Effectiveness of Banana Blossom Consumption and Oxytocin Massage in Breastfeeding Mothers on Infant Weight Gain - Intan, Dara; Hastuti, Novianti Tri; Indrawan, I Wayan Agung; Wardani, Diadjeng Setya (Indonesian Journal of Human Nutrition, 2024)
Weight gain serves as one of the indicators of the effectiveness of breastfeeding. Stimulation methods, such as consuming banana blossom and receiving oxytocin massage, have the potential to enhance breast milk production. This research aims to compare the effectiveness of these two interventions, banana blossom consumption and oxytocin massage, in breastfeeding mothers regarding infant weight increase at Dinoyo Health Center in Malang. Previous studies have demonstrated that both interventions can enhance breast milk production and infant weight; thus, this study focuses on determining which intervention is more effective. The study employed a true experimental design without a control group, utilizing a pre- and post-intervention approach during the postpartum period from days four to ten. This timeframe was selected because hormone levels, such as progesterone and estrogen, decrease, allowing for a more rapid increase in prolactin production. This approach aims to ensure that infants receive exclusive breastfeeding while promptly addressing any issues related to breast milk production. A total of 32 participants were selected through purposive sampling, with weight measurements taken at the beginning and end of the intervention. The results of the paired t-test indicated that infants of mothers who consumed banana blossom experienced an average weight gain of 246.75 g (p = 0.000). In contrast, infants whose mothers received oxytocin massage showed a weight gain of 217.81 g (p = 0.000). Further analysis with an independent t-test revealed that the consumption of banana blossom was more effective in increasing infant weight, with a mean difference in weight gain of 28.94 g (p = 0.045). This analysis confirmed a significant difference in weight gain between the two groups: mothers who consumed banana blossom had a greater increase in their infants’ weight. Future research is encouraged to explore the effectiveness of various banana blossom preparations and analyze their nutritional content to identify the most effective preparation for improving infant weight.